Islamic psychological approach to strengthen parenting resilience in mothers with postpartum baby blues in indonesia: A bibliometric analysis - Shinta, Shinta; Musslifah, Anniez Rachmawati; Putri, Dhian Riskiana; Azhar, Husain; Anniez Rachmawati Musslifah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines the incorporation of Islamic psychological ideas to enhance parenting resilience for Indonesian moms facing postpartum baby blues. This research utilized a bibliometric analysis of Scopus-indexed literature from 2014 to 2025 to systematically delineate the intellectual structure, thematic progression, and research horizons at the convergence of Islamic psychology, maternal resilience, and postpartum mental health. The research revealed 119 pertinent articles, examined using the Bibliometrix R package (v4.1) and VOSviewer (v1.6.20) for co-citation, keyword co-occurrence, and temporal trend visualization. Results indicated an increasing academic transition from individual-focused treatment methodologies to spiritually informed and culturally contextualized resilience frameworks. Islamic psychological ideas, especially tazkiyatun nafs (purification of the soul), serve as a theoretical basis connecting emotional management, cognitive restructuring, and social support systems. Spiritual activities including dhikr, sabr, syukr, and tawakkul have been demonstrated to augment maternal coping, diminish physiological stress indicators (cortisol), and boost oxytocin-mediated bonding. Moreover, familial concepts highlighting sakinah (tranquility), mawaddah (affection), and rahmah (compassion) bolster collective resilience and societal cohesion. The results of the bibliometric analysis indicated publication trends, collaborative networks, and thematic clusters related to Islamic psychology and postpartum mental health. Rather than demonstrating the clinical capacity of Islamic psychology or evaluating therapeutic outcomes, the findings primarily mapped the development of the field—showing which themes dominate. This study advances the decolonization of psychological knowledge by providing a culturally relevant framework that incorporates faith, emotion, and adaptive functioning, facilitating future evidence-based applications in clinical and community contexts.